Direct heteroarylation polymerization: guidelines for defect-free conjugated polymers. Issue 5 (29th March 2017) - Bura, Thomas; Beaupré, Serge; Légaré, Marc-André; Quinn, Jesse; Rochette, Etienne; Blaskovits, J. Terence; Fontaine, Frédéric-Georges; Pron, Agnieszka; Li, Yuning; Leclerc, Mario
Abstract : New phosphine-based ligands and DFT calculations for defect-free conjugated polymers by direct (hetero)arylation polymerization (DHAP). Abstract : Direct (hetero)arylation polymerization (DHAP) has emerged as a valuable and atom-economical alternative to traditional cross-coupling methods for the synthesis of low-cost and efficient conjugated polymers for organic electronics. However, when applied to the synthesis of certain (hetero)arene-based materials, a lack of C–H bond selectivity has been observed. To prevent such undesirable side-reactions, we report the design and synthesis of new, bulky, phosphine-based ligands that significantly enhance selectivity of the DHAP process for both halogenated and non-halogenated electron-rich and electron-deficient thiophene-based comonomers. To better understand the selectivity issues, density functional theory (DFT) calculations have been performed on various halogenated and non-halogenated electron-rich and electron-deficient thiophene-based comonomers. Calculations showed that the presence of bromine atoms decreases the energy of activation ( E a ) of the adjacent C–H bonds, allowing undesirable β-defects for some brominated aromatic units. Both calculations and the new ligands should lead to the rational design of monomers and methods for the preparation of defect-free conjugated polymers from DHAP.